The Life and Photography of Doris Ulmann - Jacobs, Philip Walker (Book collections on Project MUSE., 2001)
In this biography, based on "newly discovered letters, documents, and photographs--many published here for the first time," the author presents the life and work of Doris Ulmann, a photographer who "strove to create dignified and respectful photographic renderings of people often dishonored or ignored."--Jacket